2023
DOI: 10.3390/agriculture13010132
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Humic Acid with Fe Supplement Improved Rice, Soybean, and Lettuce Iron Fortification

Abstract: Iron (Fe) deficiency in humans, particularly in pregnant women and children, is caused by inadequate dietary Fe intake and is a global nutritional problem. Foliar fertilization is a cost-effective agronomic approach to increase Fe bioavailability in the human diet. We evaluated the effects of different Fe formulations (Fe-citrate, Fe-EDTA, FePO4, nano-Fe oxide, and humic acid (HA) with and without Fe) on growth, yield, and Fe accumulation in the edible parts of rice, soybean, and lettuce crops. Rice and soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Previous studies have found that the application of CA [39] and leonardite-derived compounds [21] improved the growth and yield of tomatoes grown in calcareous soil, probably via plant stimulation [40,41] and punctually by increasing photosynthetic parameters [42]. Similarly, the use of humic-Fe materials in soybean may be a suitable strategy for the management of Fe nutrition in calcareous soil [43], consequently leading to a reduction in Fe deficiency and an improvement in plant growth, development, and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have found that the application of CA [39] and leonardite-derived compounds [21] improved the growth and yield of tomatoes grown in calcareous soil, probably via plant stimulation [40,41] and punctually by increasing photosynthetic parameters [42]. Similarly, the use of humic-Fe materials in soybean may be a suitable strategy for the management of Fe nutrition in calcareous soil [43], consequently leading to a reduction in Fe deficiency and an improvement in plant growth, development, and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the use of humic-Fe materials in soybean may be a suitable strategy for the management of Fe nutrition in calcareous soil [43], consequently leading to a reduction in Fe deficiency and an improvement in plant growth, development, and productivity. This is because the addition of Fe together with humic complexes act as "organic chelators" that boost plant growth [41]. CA and leonardite-derived complexes exhibit various levels of complexation with Fe, promoting plant growth by inducing a physiological response [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…longifolia one of the most popular varieties (Giordano et al, 2019) and can be an optimal target for Fe bioforti cation (Mou 2009). The bioforti cation of lettuce with Fe would also provide an urgent and easy way to alleviate human Fe de ciency (Sharma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%